REGIONAL STUDIES IN SOUTHERN FEDERAL UNIVERSITY AND ITS ROLE IN THE INTEGRATION PROCESSES IN THE SOUTH OF RUSSIA - Yuriy G. Volkov; Anton V. Serikov; Viktor V. Chernous (Высшее образование в России)
The article shows how Regional studies emerged in Southern Federal University (Rostov State University successor), as a complex interdisciplinary field of higher education and scientific research. It describes the contribution of SFU to modernization and maintenance of a common scientific and educational space in the South of Russia, which is one of the foundations of Russian socio-cultural identity.